Preclinical Cartilage Changes of the Knee Joint in Adolescent Competitive Volleyball Players: A Prospective T2 Mapping Study - Roth, Christian; Hirsch, Franz Wolfgang; Sorge, Ina; Kiess, Wieland; Jurkutat, Anne; Witt, Maren; Böker, Eva; Gräfe, Daniel (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2023)
Purpose To investigate the potential effects of volleyball as a competitive sport in adolescence on the cartilage of knee joints using T2 mapping in MRI and identification of preclinical cartilage changes. Volleyball as an impact sport often leads to damage of the knee joint cartilage in adulthood. As T2 mapping is widely available and highly capable of detecting cartilage changes prior to conventional MRI sequences, such a detection may allow adolescent volleyball players to change their training regime before structural damage can occur to the cartilage and pose the risk of osteoarthritis.Materials and Methods Comparative study of the patellar, femoral, and tibial cartilage of 60 knee joints using T2 mapping on 3 T MRI. In each case, both knees of 15 adolescent competitive volleyball athletes were compared with 15 controls.Results In the group of competitive athletes, more focal cartilage changes were detected in the medial facet of the patellofemoral cartilage and in the medial femoral condyle of the knee joint cartilage (p = .01 and p <.05, respectively). Furthermore, the latter showed a diffused increase in maximal T2 mapping values (p <.04 right and p = .05 left). The distribution of changes seems to further depend on the player’s position.Conclusion In adolescent volleyball players in competitive sports, T2 mapping demonstrates early cartilage changes in both the patellofemoral and medial femoral cartilages. The distribution of lesions depends on the player’s position. Since the cascade from T2 relaxation time increase to conspicuous cartilage damage is well established, early counter-regulation (e. g., adapted training profile, targeted physiotherapy, and appropriate muscle building training) has the potential to prevent later damage.Key Points: Citation Format
Keywords: cartilage; T2 mapping; pediatric; volleyball; knee